Autonomic dysfunction in a patient with X-linked adrenoleukodystrophy. (3rd August 2018) - Zhang, Yifan; Guo, Dongmei; Tang, Yi
ABSTRACT: X-linked adrenoleukodystrophy is an inherited disease caused by abnormal accumulation of very long chain fatty acids. The diagnosis of X-linked adrenoleukodystrophy can be confirmed with the mutation of ABCD1 gene. The main symptom of the X-linked adrenoleukodystrophy is spastic paraparesis, and autonomic dysfunction is rare in X-linked adrenoleukodystrophy. Here, we presented an X-ALD case of a 46-year-old Asian male with severe autonomic dysfunction. Impairment of the autonomic nervous system may closely relate to mitochondrial defect.